Pengaruh Beban Kerja Terhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel Intervening pada PT. Perkebunan Nusantara IV Jambi - Dandy Setiawan; Sumarni Sumarni; Fitri Widiastuti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to describe the effect of workload on employee performance with work motivation as an intervening variable at PT Perkebunan Nusantara IV Jambi. This research uses quantitative methods with data collection techniques by distributing questionnaires to 70 respondents. Hypothesis testing uses descriptive analysis techniques using SmartPLS software. The results of this research indicate that workload has a significant positive influence on the performance of PT Perkebunan Nusantara IV Jambi employees. Workload has a significant positive effect on motivation. Motivation has a significant positive effect on employee performance. workload has a significant positive effect on employee performance through motivation as an intervening variable. Suggestions for this research; (1) In the employee performance variable, it is recommended that employees carry out work according to the targets that have been set, because when determining the targets it has been done carefully so that the work must be in accordance with the targets. (2) Regarding the workload variable, it is recommended that PT Perkebunan Nusantara IV Jambi further improve employee workplace facilities in order to improve the quality of their work. (3) In the work motivation variable, it is recommended that employees be more careful in carrying out work by double-checking work that has been completed so that there are no more mistakes.